UTILIZING WORKING WITH WORDS BECOME A STRATEGY IN UPGRADING ENGLISH VOCABULARY - Fredy Yunanto (Universitas Pahlawan Tuanku Tambusai, 2022)
Vocabulary mastery is very crucial in the process of learning a language, such as English. to help students increase the dominance of this vocabulary, there are various methods that can be done. one of which means using Working with Words through the Game Category. Vocabulary learning by applying the Working with Words method through Category Games showed the results: 11 students with a level of vocabulary dominance increased to 65% to 79%, with relative predicates; 7 students used the higher level of vocabulary dominance to 80% to 89%, with a Good predicate; and five students used vocabulary dominance increased to 90% to 100%, using the Very Good predicate. Keywords: Working with words, English vocabulary, game category